Classroom Management Techniques Toward Teaching Strategy Perspectives - Leovigildo Lito Mallillin; Lourdes Oliva C. Paraiso. DBA (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
This study evaluates the multifaceted role of classroom management strategies in enhancing teaching techniques and student academic performance. Specifically, it examines the intentional application of management techniques to support student success and the fundamental importance of teaching strategies within this framework. Employing a descriptive qualitative research design, the study investigates classroom management through the lens of teaching strategy perspectives. The research involved fifty (50) selected respondents. The findings reveal that classroom management techniques, when integrated into teaching strategies, effectively preempt disruptive behaviors and address complex social dynamics within the educational setting. Furthermore, these techniques contribute to the establishment of model behaviors; by demonstrating polite language, maintaining eye contact, and fostering respectful communication, educators help expand students' competencies in modern instructional environments. The results also indicate that effective management establishes critical classroom routines and behavioral rules that align with instructional content. Ultimately, the study underscores that robust classroom management creates an optimized learning environment that prioritizes students as the center of learning, thereby driving significant success in academic performance.